J-curve effect and Thailand's trade in forest products: ARDL bounds testing - Sulaiman, Chindo; Abdul Samad, Abdul Rahim (IDOSI Publications, 2014)
This paper tried to check for J-curve existence in Thailand's trade in forest products with the rest of the world. An ARDL approach to cointegration has been employed to specify trade balance model from trade equation based on the theory. Prior to the test for J-curve existence, pre-testing for unit root and cointegration test ware conducted. The results show that all the variables became stationary at first difference and cointegration exists among them. We have also assessed both the short run and long run relationships between Thailand's trade balance and its various determinants stated in the equation. The result (both in the short run and long run) shows that sustainable forest management policy's coefficients gave the expected results; income coefficients also gave expected results while the exchange rate coefficients gave contrary results as against the expected. However, the result of the J-curve effect test indicates that there are no signs of its existence and hence we concluded that it does not exists in the case Thailand's trade in forest products.